Impact des barrières linguistiques sur la sécurité des patients et la qualité des soins. Rapport final - Bowen, Sarah (Société Santé en français, 2015)

The impact of language barriers on patient safety and quality of care. Final report - Bowen, Sarah (Société Santé en français, 2015)

‘It would be nice if they could give us more language’ – Serving South Africa’s multilingual patient base - Deumert, Ana (Social Science & Medicine, 2010)

The language barrier : the overlooked challenge to equitable health care - Hussey, Nadia (South African Health Review, 2012)
This chapter examines the effects of language barriers on the access of patients and communities to quality health care. It also looks at communication challenges experienced by health professionals that provide this care. Using a case study of a rural hospital, the chapter highlights some of the challenges posed by the language barrier and explores current methods that English-speaking health professionals at this hospital use to overcome these difficulties. The case study findings indicate that the language barrier decreases work efficiency and the provision of holistic treatment. It makes communication time consuming, which increases frustration levels and decreases empathy, approachability and confidentiality. Current methods for overcoming problems include the use of untrained and ineffective interpreters - usually overworked nurses; linguistic codeswitching; and the use of a selection of key isiXhosa vocabulary. These methods have many drawbacks and are not suitable or sustainable. Recommendations for improving communication include the promotion of a culture of multilingualism, which includes language education as a part of professional development and the employment of trained interpreters. For multilingualism to occur, more research needs to be conducted, and the political will to address this problem must be demonstrated. Overcoming the language barrier needs to be prioritised and commitment must be made to implementing strategies that provide a multilingual patient base with a multilingual healthcare service.

Language and culture in the caregiving of people with dementia in care homes - What are the implications for well-being? A scoping review with a Welsh perspective - Martin, Conor; Woods, Bob; Williams, Siôn (Journal of Cross-Cultural Gerontology, 2019)
The loss of language skills is one of the most challenging aspects of living with dementia. This is particularly true for bilingual individuals, who have difficulty in maintaining fluency in more than one language. Language and culture overlap greatly, with potential implications for the well-being of people with dementia (PWD) being cared for in their ‘second’ language or culture. Our aim was to review the available relevant literature, together with an examination of the potential effects of linguistic incongruity on healthcare in general for Welsh speakers in Wales. A literature search yielded 50 articles, which were analysed using the scoping review methodological framework. We found that the presence of cultural and linguistic congruity was beneficial for PWD living in care homes, and that their absence was detrimental. The absence of linguistic congruity is a strong predictor for decreased well-being in people in such settings, due to communication barriers between residents and carers, which result mainly from the loss of PWD’s second language skills. Such barriers may lead to inappropriate care, e.g. being unable to obtain help to self-care, as well as social isolation. This review suggests that strategies need to be developed across the world to accommodate bilingual individuals requiring a care home for their dementia needs. There is a particular dearth of research regarding the influence of bilingualism on the experience of dementia care in those areas of the UK where the indigenous population are most likely to be bilingual (i.e. parts of Wales).

Implementing the Evidence for Language-appropriate Health Care Systems: The Welsh Context - Roberts, Gwerfyl W.; Burton, Christopher R. (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)
Like Canada, Wales, UK is a bilingual nation: the Welsh language is an important part of its national identity and legislative framework. This has implications for the delivery of public sector services, particularly in the context of health and social care, where responding to the language needs of service users is fundamental to quality health care provision. Nevertheless, despite the strengthening policy commitment for a whole-system approach towards enhancing Welsh language services, there is a paucity of evidence to guide best practice in organizational planning in health care settings. This commentary outlines the context and significance of bilingual health care provision in Wales and the implications for building and embedding the evidence base. It calls for further work to translate our knowledge and understanding of language-appropriate practice to provide more effective and sensitive health care services; and to close the implementation gap between evidence and practice. Given the relevance of this challenge for health care providers in Canada who plan and deliver services for French-language minorities, this approach has resonance across our research communities. Thus, in our common pursuit to establish integrated knowledge translation research for language-appropriate health care systems, this commentary offers a focus for reflection, discussion and collaborative action. KEY WORDS: Knowledge management; language; minority health; organizational change; Wales

Comparing mental health of Francophones in Canada, France, and Belgium: 12-month and lifetime rates of mental health service use (part 2) - Tempier, Raymond; Vasiliadis, Helen-Maria; Gilbert, Fabien; Demyttenaere, Koen; Bruffaerts, Ronny; Lépine, Jean-Pierre; Gasquet, Isabelle; Lepnurm, Marje; Lesage, Alain; Puchala, Chassidy; Mosier, Karen; Kovess-Masféty, Viviane (The Canadian Journal of Psychiatry, 2010)
Objectives: To compare 12-month and lifetime service use for common mental disorders in 4 francophone subsamples using data from national mental health surveys in Canada, Quebec, France, and Belgium. This is the second article in a 2-part series comparing mental disorders and service use prevalence of French-speaking populations. Methods: Comparable World Mental Health-Composite International Diagnostic Interviews (WMH-CIDI) were administered to representative samples of adults (aged 18 years and older) in Canada during 2002 and in France and Belgium from 2001 to 2003. Two groups of francophone adults in Canada, in Quebec (n = 7571) and outside Quebec (n = 500), and respondents in Belgium (n = 389) and France (n = 1436) completed the French version of the population survey. Prevalence rates of common mental health service use were examined for major depressive episodes and specific anxiety disorders (that is, agoraphobia, social phobia, and panic disorder). Results: Overall, most francophones with mental disorders do not seek treatment. Canadians consulted more mental health professionals than their European counterparts, with the exception of psychiatrists. Conclusions: Patterns of service use are similar among francophone populations. Variations that exist may be accounted for by differences in health care resources, health care systems, and health insurance coverage.

Enjeux des services sociaux et de santé en contexte bilingue ou multilingue national. Revue de littérature - van Kemenade, Solange; Forest, Mariève (Secrétariat national du Consortium national de formation en santé, 2015)